Effect of Corrupt Behavior of the Forestry Bureaucrats on the Forest Sustainability - Sudarsono Soedomo (Jurnal Manajemen Hutan Tropika, 2005)
This article show that corrupt bureaucrats do not always result in a negative effect on the forest sustainability. Even under a certain condition, a corrupt behavior may result in a positive effect on the forest sustainability. An inappropriate policy is more important a cause of the forest sustainability than a corrupt behavior. Therefore, fixing this structural mistake needs to be prioritized in combating the forest destruction, for this structural mistake is the real primary cause of the forest destruction in Indonesia. Fixing this structural mistake is much more effective in combating the forest destruction than finding honest bureaucrats.